Real-world assessment of diquafosol in dry eye patients with risk factors such as contact lens, meibomian gland dysfunction, and conjunctivochalasis: subgroup analysis from a prospective observational study - Yamaguchi M (Dove Medical Press, 2015)
Masahiko Yamaguchi,1 Takeshi Nishijima,2 Jun Shimazaki,3 Etsuko Takamura,4 Norihiko Yokoi,5 Hitoshi Watanabe,6 Yuichi Ohashi1 1Department of Ophthalmology, Ehime University School of Medicine, Ehime, 2Department of Safety Vigilance Group, Santen Pharmaceutical Co., Ltd., Osaka, 3Department of Ophthalmology, Tokyo Dental College, Ichikawa General Hospital, Chiba, 4Department of Ophthalmology, School of Medicine, Tokyo Women’s Medical University, Tokyo, 5Department of Ophthalmology, Kyoto Prefectural University of Medicine, Kyoto, 6Department of Ophthalmology, Kansai Rosai Hospital, Hyogo, Japan Purpose: To evaluate the efficacy and safety of diquafosol (DQS) ophthalmic solution in dry eye (DE) patients wearing contact lenses (CLs) or with concomitant meibomian gland dysfunction (MGD) or conjunctivochalasis in a real-world setting. Patients and methods: From a cohort of patients enrolled in a prospective observational study, DE patients who met the Japanese diagnostic criteria and who received DQS as a monotherapy were extracted and stratified according to the presence or absence of CL use, MGD, and conjunctivochalasis. Corneal and conjunctival fluorescein staining score, tear film break-up time, total symptom score (12 DE-related subjective symptoms), patient-reported outcomes, and adverse reactions were investigated. Results: DQS treatment resulted in significant improvement in total symptom score, corneal and conjunctival fluorescein staining score, and tear film break-up time without significant differences between patient subgroups with versus without CL use, MGD, or conjunctivochalasis. Comparable proportions of patients perceived symptomatic improvements in all subgroups. There were no adverse reactions specifically associated with the CL use or any comorbidity of MGD or conjunctivochalasis. Conclusion: DQS can be used effectively and safely as a monotherapy for the treatment of DE patients wearing CLs or with concomitant MGD or conjunctivochalasis. Keywords: clinical practice, dry eye syndrome, patient-reported outcome, Diquas®